Learning from patient and site perspectives to develop better digital health trials: Recommendations from the Clinical Trials Transformation Initiative - Cindy Geoghegan; Virginia Nido; Angie Botto-van Bemden; Zachary Hallinan; Les Jordan; Lindsay S. Kehoe; Steve L. Morin; Amanda Niskar; Petros G. Okubagzi; William A. Wood (Contemporary Clinical Trials Communications, 2020)
In order to harness the potential of digital health technologies to enhance the quality of clinical research, it is critical to first understand how to engage patients and research sites when planning and conducting digital health trials. To pave the way for the more effective use of digital health technologies in trials, the Clinical Trials Transformation Initiative has developed the first comprehensive, evidence-based set of recommendations for incorporating patient and site perspectives in digital health trials. While directed primarily at sponsors, these recommendations are expected to be valuable for all stakeholders including investigators.